The spider-like katydid Arachnoscelis (Orthoptera: Tettigoniidae: Listroscelidinae): anatomical study of the genus - Montealegre-Z, Fernando; Cadena-Castañeda, Oscar J.; Chivers, Benedict (Zootaxa, 2013)
This paper provides some observations on the anatomy of the neotropical katydid Arachnoscelis arachnoides Karny (In-secta: Orthoptera: Tettigoniidae). Arachnoscelis is a genus of predaceous katydids that comprise species that resemble spi-ders in their general body appearance. The type species, A. arachnoids, was described in 1891 from a single male collected in Colombia. Following the original description, these creatures were never found again, and were thought to have gone extinct or mistakenly assigned to the type locality. But between 1891 and 2012 four more species were described and in-correctly assigned to Arachnoscelis based on a similarity of body form. In this paper we present an anatomical comparai-son of Arachnoscelis and its relatives, and propose that Arachnoscelis should be treated as a monotypic genus. This implies that other species previously described in Arachnoscelis, should be placed in different genera.